Cross‐sectional study of UK horse owner's purchase and euthanasia decision‐making for their horse. (28th January 2021) - Clough, Harriet; Roshier, Mandy; England, Gary; Burford, John; Freeman, Sarah
Abstract: Background : This cross‐sectional study aimed to investigate factors affecting horse owners' purchase and euthanasia decisions that had been identified in a qualitative study. Methods : An online survey on horse owners' purchase and euthanasia decisions and experiences was distributed using snowball sampling. Inclusion criteria were previous experience of purchase or euthanasia decisions. Descriptive data analyses (mean, median, mode and frequency percentages) were performed. Results : There were 451 participants from the UK and Ireland, 97% were female with a median age of 45 years. Participants most frequently did not seek any advice when deciding what type of horse to purchase (38.6%, 169/438) or if it was priced appropriately (48.7%, 214/439). Most participants were satisfied with their purchase and would purchase their horse again (84.9%, 370/436). The most frequent reasons for euthanasia were injury/illness with low chance of survival (55.2%, 201/364), poor quality of life (42.6%, 155/363) and long‐term injury (35.7%, 130/364). Most participants sought advice or guidance when making end‐of‐life decisions (87.5%, 328/375), and 55% (243/440) had a euthanasia plan in place. Conclusions : Owners show limited advice‐seeking behaviour on key aspects of purchase decisions. Owners frequently seek advice on euthanasia decisions, and the majority of decisions were based on welfare concerns.